THE EFFECT OF FISHBOWL TECHNIQUE AND STUDENTS’ INTEREST TOWARD THE EIGHT GRADE STUDENTS’ SPEAKING ABILITY OF SMP XAVERIUS 1 PALEMBANG - Andika, Andika (English Community Journal, 2018)
This study was purposed at investigating the effect of Fishbowl technique and students’ Interest toward the eighth Grade students’ speaking ability. The population of this study was 300 students of SMP Xaverius 1 Palembang. From the population, there were 30 students taken as sample of experimental group and 30 students were as control group. The sample was taken using two stages random sampling. In carrying out the research, the writer used a factorial group design. Finnaly the calculation using a two-way ANOVA was used to measure an interaction between fishbowl technique and students interest on their speaking ability. Test of Between-Subjects Effects analyses, the significant value of the techniques (fishbowl and conventional) and the students’ interest were 0.422, the probability sig. of technique was 0.175, and the interaction between high and low interest was 0.097 which higher than the significant level of p-value 0.05, it meant that there was no a significant interactions between students’ interest and techniques. So, the research hypothesis that stated “there is no an interaction between fishbowl technique and interest toward students’ speaking ability” was accepted and the null hypothesis was not rejected based on the data finding on chapter four.